Recommendations and Protocols for the Use of the Isotope Ratio Infrared Spectrometer (Delta Ray) to Measure Stable Isotopes from CO2: An Application to Volcanic Emissions at Mount Etna and Stromboli (Sicily, Italy). (1st August 2020) - Boudoire, G.; Grassa, F.; Giuffrida, G.; Liuzzo, M.
Abstract : Among major volatiles released from the Earth's interior, CO2 is an important target for the international community. The interest is keenly motivated by the contribution of CO2 in the Earth's carbon budget and its role on past, current, and future climate dynamics. In particular, the isotopic signature of CO2 is fundamental to characterize the source of this gas and its evolution up to the atmosphere. The recent development of new laser-based techniques has marked an important milestone for the scientific community by favoring both high-frequency and in situ stable isotope measurements. Among them, the Delta Ray IRIS (Thermo Scientific Inc., Waltham, USA) is one of the most promising instruments thanks to its high precision, its limited interferences with other gaseous species (such as H2 S and/or SO2 ), and its internal calibration procedure. These characteristics and the relative easiness to transport the Delta Ray IRIS have encouraged its use on the field to analyze volcanic CO2 emissions in recent years but often with distinct customized protocols of measurements. In this study, various tests in the laboratory and on the field have been performed to study the dependence of CO2 isotope measurements on analytical, instrumental, and environmental conditions. We emphasize the exceptional ability of the Delta Ray IRIS to perform isotope measurements for a large range of CO2 concentration (200 ppm–100%) thanks to a dilution system and to get a reliable estimation of the real CO2 content from the diluted one. These tests lead to point out major recommendations on the use of Delta Ray IRIS and allow the development of adapted protocols to analyze CO2 emissions like in volcanic environments.